Aged Human Dermal Extracellular Matrix as an Innovative Scaffold for Aging on Chip Model - Fernández-Carro, Estibaliz; Remacha, Ana Rosa; Orera, Irene; Lattanzio, Giuseppe; Garcia-Barrios, Alberto; del Barrio, Jesús; Alcaine, Clara; Ciriza, Jesús (Jornada de Jóvenes Investigadores del I3A, 2024)
Currently, there is a growing demand for developing innovative biomaterials that represent skin microenvironment more realistically. Here, we present an optimised protocol to extract and characterize an innovative human adult dermal extracellular matrix scaffold to represent the dermal layer in advanced 3D skin models.